2011
DOI: 10.1051/0004-6361/201014423
|View full text |Cite
|
Sign up to set email alerts
|

Orion KL: the hot core that is not a “hot core”

Abstract: We present sensitive high angular resolution submillimeter and millimeter observations of torsionally/vibrationally highly excited lines of the CH 3 OH, HC 3 N, SO 2 , and CH 3 CN molecules and of the continuum emission at 870 and 1300 μm from the Orion KL region, made with the Submillimeter Array (SMA). These observations and SMA CO J = 3−2 and J = 2−1 imaging of the explosive flow originating in this region suggest that the molecular Orion "hot core" is a pre-existing density enhancement heated from the outs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 53 publications
8
99
0
Order By: Relevance
“…However, in the last years Arce et al (2008) and Codella et al (2009) detected CH 3 CN towards the molecular outflow driven by the low-mass YSO L1157-mm, hence showing that also this species can be altered by the passage of bow shocks, although with abundances much lower than in hot cores and hot corinos around high-and low-mass YSOs (e.g., Olmi et al 1993;Beltrán et al 2005;Bottinelli et al 2007). Additionally, Zapata et al (2011) recently proposed that CH 3 CN emission in Orion-KL is also excited by shocks. In the present case, the velocity gradient detected in CH 3 CN could be due to outflowenvelope interactions as already seen in low-mass star class 0 sources (Beltrán et al 2004b;Arce & Sargent 2005;Lee et al 2005) in other molecular species.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last years Arce et al (2008) and Codella et al (2009) detected CH 3 CN towards the molecular outflow driven by the low-mass YSO L1157-mm, hence showing that also this species can be altered by the passage of bow shocks, although with abundances much lower than in hot cores and hot corinos around high-and low-mass YSOs (e.g., Olmi et al 1993;Beltrán et al 2005;Bottinelli et al 2007). Additionally, Zapata et al (2011) recently proposed that CH 3 CN emission in Orion-KL is also excited by shocks. In the present case, the velocity gradient detected in CH 3 CN could be due to outflowenvelope interactions as already seen in low-mass star class 0 sources (Beltrán et al 2004b;Arce & Sargent 2005;Lee et al 2005) in other molecular species.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to mention that recently Zapata et al (2011) have also found some evidence for external heating towards the Hot Core. These two dense regions of the Orion-KL nebula seem to be associated with the dynamical event that occurred 500 years ago.…”
Section: From Methanol and Methyl Cyanide High-resolution Studiesmentioning
confidence: 95%
“…A.5). On small scales, interferometric observations of Orion-KL also detect a compact SO 2 emission peak Zapata et al 2011) and strong extended emission of 34 SO 2 to mm2 (Beuther et al 2005). -SO (sulphur monoxide) has multiple strong emission peaks towards HC, NE, mm3a, and mm3b and exhibits strong self-absorption in mm2 ( Fig.…”
Section: Line Imagingmentioning
confidence: 98%
“…4.2.2. Beuther et al (2004); (g) Menten & Reid (1995); (h) Blake et al (1996); (i) Tang et al (2010); ( j) Favre et al (2011a); (k) Murata et al (1992); (l) Zapata et al (2011);(m) Eisner et al (2008) ; (n) Wright et al (1992); (o) Beckwith et al (1978).…”
Section: Continuum Emissionmentioning
confidence: 99%